Species of Sulfur in Sour Gas Reservoir: Insights from In Situ Raman Spectroscopy of S–H2S–CH4–H2O System and Its Subsystems from 20 to 250°C - Yifan Yu; Wenxuan Hu; I-Ming Chou; Lei Jiang; Ye Wan; Yiqun Li; Yang Xin; Xiaolin Wang (Geofluids)
Thermochemical sulfate reduction (TSR) is the most important mechanism for the generation of high-concentration H2S in gas reservoirs. Sulfur speciation in sour gas is one of the key factors controlling the rate and extent of TSR in gas reservoirs. However, experimental studies on S species in sour gas are limited due to the toxicity and corrosion of S and H2S. Fused silica capillary capsules (FSCCs) are inert to S and H2S and, therefore, were employed in this study as microreactors containing the S–H2S–CH4–H2O system and its subsystems, representing the composition of sour gas. The in situ Raman spectra of each system were collected continuously during the process of heating from 20°C to 250°C. The results showed the following: (1) a Raman peak at 2500 cm−1 was detected in the liquid S phase of the S–H2S–CH4 –H2O system at 120–250°C, which was attributed to H2Sn. A Raman band at ~533 cm−1 was detected in the aqueous phase of the S–H2S–H2O–CH4 system at 250°C and was assigned to S3−, suggesting that S3− and H2Sn are important S species in sour gas reservoirs at elevated temperatures. (2) The Raman peak at 2500 cm−1 disappeared at 20°C, indicating that H2Sn decomposes into S and H2S. During gas extraction, the decomposition of H2Sn will cause S deposition in pipelines. (3) In addition to S3−, H2Sn could be the intermediate valence S species involved in the TSR reaction.